2018
DOI: 10.1002/jcb.27716
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier tightening by a cell‐penetrating antibody to Bin1, a candidate target for immunotherapy of ulcerative colitis

Abstract: Patients afflicted with ulcerative colitis (UC) are at increased risk of colorectal cancer. While its causes are not fully understood, UC is associated with defects in colonic epithelial barriers that sustain inflammation of the colon mucosa caused by recruitment of lymphocytes and neutrophils into the lamina propria. Based on genetic evidence that attenuation of the bridging integrator 1 (Bin1) gene can limit UC pathogenicity in animals, we have explored Bin1 targeting as a therapeutic option. Early feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 50 publications
2
41
0
Order By: Relevance
“…Based on the observation we asked whether lowering the levels of BIN1 with specific antibodies would provide protection against UC. Our group found that the Bin1 antibody (99D) could exert drug‐like properties in an animal model of UC . Given the clinical genetics associating BIN1 with AD, and their molecular connections to Tau, we formed the hypothesis that anti‐Bin1 might be used as a drug to block Tau accumulation and disease pathology in AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the observation we asked whether lowering the levels of BIN1 with specific antibodies would provide protection against UC. Our group found that the Bin1 antibody (99D) could exert drug‐like properties in an animal model of UC . Given the clinical genetics associating BIN1 with AD, and their molecular connections to Tau, we formed the hypothesis that anti‐Bin1 might be used as a drug to block Tau accumulation and disease pathology in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The fougaro system may be a mechanism to recycle or remove molecules from the nucleus to the external medium. 20 The ubiquitin-proteasome system degrades misfolded proteins including those implicated in AD. 47 A characteristic of AD is a poor proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…Bin1 monoclonal antibodies. We used the therapeutic 99D Bin1 monoclonal antibody for our study (Thomas et al 2016(Thomas et al , 2019a. The antibody 99D recognizes an epitope within the C-terminal Myc binding domain encoded by exon 13 (Wechsler-Reya et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Mice induced with UC had severe lesions throughout the mucosa, high-level neutrophil and lymphocyte infiltration into the mucosal and submucosal areas, and loss of crypts. Whereas, animals treated with the cell penetrating Bin1 mAb protects against UC by directly improving colonic epithelial barrier function that limit gene expression and cytokine programs associated with colonic inflammation (Thomas et al 2016;2019a). In this paper, we report progress in how Bin1 mAb treatment protects against UC; specifically, it protects enteric neurons thereby preventing bowel movement dysfunction, and that it promotes formation of a healthy gut microbiome.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, a therapy targeting BIN1 reportedly improved the mucosal barrier function and protected the integrity of the lymphoid follicle, which offers a novel strategy to treat ulcerative colitis and possibly limits the risks for colorectal cancer. 76 Another study indicated that phosphodiesterase 5 inhibition improves contractile function and restores transverse tubule loss and catecholamine responsiveness in HF. A related molecular switch for the loss of T-tubules in HF and their restoration following phosphodiesterase 5 inhibition involves BIN1.…”
Section: Novel Diagnosis and Therapy Targeted For Bin1mentioning
confidence: 99%